The Role of Television in the Development of English Language Competencies in Primary School Pupils within the Bamenda III Municipality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The Educational system in Cameroon has undergone significant changes regarding the use of Information Communication and Technology (ICT) for teaching and learning. With the constant growth in understanding ICTs in governance, business and in the development process, ICT has increased the scope of learning processes. It provides new learning material. Thus, (ICT) in English language learning and teaching has been the researchers, focus of attention It is based on this prelude that this study seeks to find out the positive effects of television in the development of English language competencies in primary school pupils within the Bamenda III Municipality. The study used the survey research design which comprises of cross sectional and quantitative designs. The data used was solicited from primary sources which is through questionnaires and interviews. A sample of 110 respondents mainly selected teachers from public, lay private and mission nursery and primary schools in Bamenda III municipality with a span from January to November, 2020. The study employed the descriptive and inferential statistics using the ANOVA multiple regression approach. The findings of the study revealed that an increase in the use of television will lead to a moderate increase in the development of language skills. The p value=0.004 which is less than 0.05 indicating a significant relationship between the use of television and the development of language skills. From the findings, this study recommended that the Teachers should undergo pedagogic training on the use of ICT in teaching. Teachers should be encouraged to use ICT tools often in passing out knowledge. Schools should be equipped with a complete ICT unit. Teachers should be sensitize on the importance of ICT in teaching. They should learn to be able to identify their learning needs, define their learning strategies, develop and implement a learning plan and evaluate the learning gained, with or without the help of others (by using ICT tools). The government and stakeholders and parents should reinforce use of ICT in schools through proper monitoring and evaluation.